2021
DOI: 10.1371/journal.pone.0249559
|View full text |Cite
|
Sign up to set email alerts
|

Are there sex differences in physiological parameters and reaction time responses to overload in firefighters?

Abstract: Male and female firefighters work side-by-side in the same in strenuous and risky conditions. Anthropometrics, physiological, and reaction time (mean of reaction time -MRT-, and errors made -E) parameters of 12 Female and 13 Male firefighters were compared. Effect of overload (step test with and without equipment) on the MRT and E were analyzed on 3 trials (T1 = 1-1s, T2 = 0.5-1s, T3 = 0.5–0.5s), compared with a pre-test condition (basal). T-test between males and females was applied to assess differences (p&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Few studies have mentioned differences concerning occupational aspects between female and male firefighters. Perroni et al [ 46 ] reported that due to physiological sex differences, female firefighters have a higher level of physical demands to perform expected firefighter tasks. In addition, a working group of IARC recently concluded that a lack of proper personal protective equipment (PPE) fitting is likely among females, which could result in more significant contamination and exposure [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have mentioned differences concerning occupational aspects between female and male firefighters. Perroni et al [ 46 ] reported that due to physiological sex differences, female firefighters have a higher level of physical demands to perform expected firefighter tasks. In addition, a working group of IARC recently concluded that a lack of proper personal protective equipment (PPE) fitting is likely among females, which could result in more significant contamination and exposure [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the rate of female participation in physically demanding occupations such as the military and firefighting has increased (Anderson et al, 2022;Perroni et al, 2021), even reaching the 10-15% of wildland fire crews in the United States (Sol et al, 2018). Despite this fact, there is still a lack of studies on the role of sex in physical condition, work capacity and thermoregulation in professional sectors.…”
Section: Introductionmentioning
confidence: 99%